Transcultural adaptation and validation of Persian Version of Patient Assessment of Chronic Illness Care (PACIC-5As) Questionnaire in Iranian older patients with type 2 diabetes - Sahar Maroufi; Leila Dehghankar; Ahad Alizadeh; Mohammad Amerzadeh; Seyedeh Ameneh Motalebi (BMC, 2024)
Abstract Background The Patient Assessment of Chronic Illness Care (PACIC-5As) questionnaire has been designed to evaluate the healthcare experiences of individuals with chronic diseases such as diabetes. Older adults are at higher risk for diabetes and its associated complications. The aim of this study was transcultural adaptation and evaluation of the validity and reliability of the PACIC-5As questionnaire in older patients with diabetes residing in Qazvin City, Iran. Method In this validation study, we recruited 306 older patients with diabetes from Comprehensive Health Centers in Qazvin, Iran. The multi-stage cluster sampling technique was used to choose a representative sample. The PACIC-5As questionnaire was translated into Persian using the World Health Organization (WHO) standardized method. The validity (face, content, and construct) and reliability (Cronbach's alpha) of the PACIC-5As were assessed. Data analysis was conducted using R software and the Lavaan package. Results The mean age of the older patients was 69.99 ± 6.94 years old. Most older participants were female (n = 180, 58.82%) and married (n = 216, 70.59%). Regarding face validity, all items of PACIC-5As had impact scores greater than 1.5. In terms of content validity, all items had a content validity ratio > 0.49 and a content validity index > 0.79. The results of confirmatory factor analysis demonstrated that the model exhibited satisfactory fit across the expected five factors, including assess, advise, agree, assist, and arrange, for the 25 items of the PACIC-5As questionnaire. The Cronbach's alpha coefficient for the PACIC-5As questionnaire was 0.805. Conclusion This study indicates that the Persian version of the PACIC-5As questionnaire is valid and reliable for assessing healthcare experiences in older patients with diabetes. This means that the questionnaire can be effectively used in this population.